Consumption of predefined 'Nordic' dietary items in ten European countries – an investigation in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Issue 12 (3rd March 2014) - Roswall, Nina; Olsen, Anja; Boll, Katja; Christensen, Jane; Halkjær, Jytte; Sørensen, Thorkild IA; Dahm, Christina C; Overvad, Kim; Clavel-Chapelon, Françoise; Boutron-Ruault, Marie C; Cottet, Vanessa; Teucher, Birgit; et al.
Abstract Objective Health-beneficial effects of adhering to a healthy Nordic diet index have been suggested. However, it has not been examined to what extent the included dietary components are exclusively related to the Nordic countries or if they are part of other European diets as well, suggesting a broader preventive potential. The present study describes the intake of seven a priori defined healthy food items (apples/pears, berries, cabbages, dark bread, shellfish, fish and root vegetables) across ten countries participating in the European Prospective Investigation into Cancer and Nutrition (EPIC) and examines their consumption across Europe. Design Cross-sectional study. A 24 h dietary recall was administered through a software program containing country-specific recipes. Sex-specific mean food intake was calculated for each centre/country, as well as percentage of overall food groups consumed as healthy Nordic food items. All analyses were weighted by day and season of data collection. Setting Multi-centre, European study. Subjects Persons (n 36 970) aged 35–74 years, constituting a random sample of 519 978 EPIC participants. Results The highest intakes of the included diet components were: cabbages and berries in Central Europe; apples/pears in Southern Europe; dark bread in Norway, Denmark and Greece; fish in Southern and Northern countries; shellfish in Spain; and root vegetables in Northern and Central Europe. Large inter-centre variation, however, existed in some countries. Conclusions Dark bread, root vegetables and fish are strongly related to a Nordic dietary tradition. Apples/pears, berries, cabbages, fish, shellfish and root vegetables are broadly consumed in Europe, and may thus be included in regional public health campaigns.